Klasifikasi Maqasid dalam Tafsir Maqasidi - Abd. Muqit (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Maqasid has the aim of realizing benefits, goodness and pleasure for humans which is called jalb al-manafi', as well as avoiding or preventing damage and evil. Maqasid shari'ah has been rerouted to the classics, but in its development, Islamic scholarship has stagnated. It was only in the contemporary era that it developed again. It is against this background that the research was conducted. The results of the study conclude that maqasid shari'ah is to realize the benefits for humans and prevent humans from mafsadah (damage), both in this world and the hereafter. Maqasid sharia is classified in aspects of human life, namely hifdhu al-Din (religious protection), hifdhu nafs (life protection), hifdhu 'aqli (protection of reason), hifdhu nasl (protection of offspring), hifdhu mal (protection of property). However, this maqasid is not partial but must be interconnected with one another. Then in terms of strong and low values, maslahah is divided into three, namely daruriyah (primary), hajiyah (needs), and tahsiniyah (secondary). There are maslahah that are amah, distinctive, and juz'i.